An in-vitro study on the effect of carica papaya crude aqueous extract on the voltage-gated sodium channel (VGSC) mediated motility on mda-mb 231 breast cancer cell line - Amira Raudhah, Abdullah (Pusat Pengajian Sains Perubatan, 2013)
Voltage-gated sodium channel (VGSC) in the line of suitable target markers for cancer therapy has been extensively studied by researchers over recent years. Variety of study provides suggestive evidence on the involvement of VGSC in regulating growth and expansion of cancer cell together with its role in metastasis. The predominant and highly expressed VGSC in breast cancer cells is the neonatal splice variant (nNavl.5). We aimed to target the specific VGSC markers, nNavl .5 gene expression towards controlling the rate of metastasis in breast cancer. Carica papaya is our choice candidate in down regulating the gene expression of nNav 1.5 due to its local anesthetic properties as well as well-known role in exhibiting the anti-cancer or anti-proliferative properties. MTI assay and Trypan Blue assay procedure were conducted to test the toxicity and viability of MDA-MB-231 breast cancer cell in response to C. papaya aqueous crude extract treatment at 0.1 μg/mL, 1.0 μg/mL and 10.0 μg/mL. Moreover, we performed the lateral motility assay and PCR in order to determine the effects of C. papaya treatment at similar concentration on MDA-MB-231 cells motility and nNavl.5 gene. Results and data analysis provide suggestive evidence that at the concentrations tested, the aqueous crude extract of C. papaya was non-toxic and also did not affect the growth of MDA-MB 231 cells. Interestingly, whilst the extract was none effective on the cell's growth, lateral motility of MDA-MB-231 cells was reduced, suggesting that the effect of the extract on reducing motility was indisputable. Consequently, the expression of nNavl.5 gene was down-regulated as the concentration of C. papaya treatment increased, suggesting the mode of action of the extract on reducing motility might